PENDAMPINGAN MASYARAKAT KAMPUNG MASPATI DALAM MENULIS SEJARAH KAMPUNG SEBAGAI MEDIA PROMOSI WISATA KOTA SURABAYA - Purnawan Basundoro; Laode Rabani (Jurnal Layanan Masyarakat (Journal of Public Services), 2021)
AbstractSeveral kampong in the Surabaya city are currently used as tourist destinations, by offering the uniqueness of the kampong. One of the kampong that has succeeded in becoming a tourist destination is Kampung Maspati, which is located in the city center. The ancientness of the kampong is offered to tourists so they are interested in visiting it. One of the weaknesses, Kampung Maspati does not have a historical narrative that explains the development of the kampong from the past until now. The Department of History, Faculty of Humanties, Universitas Airlangga organizes community service activities to assist in writing village history, o increase the promotion of kampong tourism. This paper was written in reference to these activities. The methods used to explain are field work, in-depth interviews, the use of library collections, and assitances. The findings obtained from these activities are that the understanding of the people of Kampung Maspati on the history of the kampung is still not good, so that continuous assistance is needed. This kind of activities also needs to be extended to others kampong because currently there are still many historic kampong in the Surabaya city that do not yet have historical narratives. This activity needs to be done so that the promotion of kampong tourism can be improved.Keyword: kampong tourism, promotion, Maspati, SurabayaAbstrakBeberapa kampung di kota Surabaya saat ini dijadikan sebagai tujuan wisata, dengan menawarkan keunikan yang ada di kampung tersebut. Salah satu kampung yang berhasil menjadi tujuan wisata adalah Kampung Maspati yang terletak di pusat kota. Kekunoan kampung ditawarkan kepada wisatawan sehingga mereka tertarik untuk mengunjunginya. Salah satu kelemahan, Kampung Maspati tidak memiliki narasi sejarah yang menjelaskan perkembangan kampung sejak dulu sampai sekarang. Departemen Ilmu Sejarah Fakultas Ilmu Budaya Universitas Airlangga menyelengarakan  kegiatan pengabdian masyarakat pendampingan menulis sejarah kampung, untuk meningkatkan promosi wisata kampung. Makalah ini ditulis mengacu kepada  kegiatan tersebut. Metode yang digunakan untuk menjelaskan adalah kerja lapangan, wawancara mendalam,  penggunaan koleksi pustaka, dan pendampingan.Temuan yang diperolah dari kegiatan tersebut bahwa pemahaman masyarakat Kampung Maspati terhadap sejarah kampung masih kurang sehingga perlu dilakukan pendampingan secara berkesinambungan. Kegiatan semacam ini juga perlu diperluas ke kampung lain karena saat ini masih banyak kampung bersejarah di Kota Surabaya yang belum memiliki narasi sejarah. Kegiatan itu perlu dilakukan agar promosi wisata kampung bisa ditingkatkan.Kata kunci: wisata kampung, promosi, Maspati, Surabaya